2017
DOI: 10.1111/liv.13386
|View full text |Cite
|
Sign up to set email alerts
|

Transient von Willebrand factor‐mediated platelet influx stimulates liver regeneration after partial hepatectomy in mice

Abstract: A rapid but transient VWF-dependent platelet influx into the liver remnant drives platelet-mediated liver regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 26 publications
2
53
0
Order By: Relevance
“…Nevertheless, platelets could be shown to play a central role during liver regeneration, most likely by releasing their cargo to promote cell‐cycle progression and proliferation . Recently, Kirschbaum et al demonstrated that platelet accumulation within the liver to promote liver regeneration is specifically relevant in the very early phase of liver regeneration after partial hepatectomy in mice . Within this investigation, we report on human data on vWF‐dependent platelet accumulation during liver regeneration.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Nevertheless, platelets could be shown to play a central role during liver regeneration, most likely by releasing their cargo to promote cell‐cycle progression and proliferation . Recently, Kirschbaum et al demonstrated that platelet accumulation within the liver to promote liver regeneration is specifically relevant in the very early phase of liver regeneration after partial hepatectomy in mice . Within this investigation, we report on human data on vWF‐dependent platelet accumulation during liver regeneration.…”
Section: Discussionmentioning
confidence: 84%
“…Kirschbaum et al were able to provide solid evidence for a critical relevance of vWF for platelet adhesion within the regenerating liver . Indeed, both blocking vWF through an antibody and knockout of vWF lead to reduced liver regeneration in affected mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Platelets have now been shown to have roles in immunity, including antimicrobial defense, 1 and in cancer growth and metastasis, [2][3][4] tumor angiogenesis, 5 lymphangiogenesis, 3,6 inflammatory diseases, [7][8][9] wound healing, 10 liver regeneration, 11 and neurodegeneration. 12 Despite these numerous and varied roles of platelets in mammalian physiology and pathology, disorders of platelet number or function in general manifest most clearly as either bleeding or thrombosis.…”
Section: Introduction To a Series Of Reviews On Clinical Platelet Dismentioning
confidence: 99%